2017
DOI: 10.1093/nar/gkx942
|View full text |Cite
|
Sign up to set email alerts
|

Thioflavin T binds dimeric parallel-stranded GA-containing non-G-quadruplex DNAs: a general approach to lighting up double-stranded scaffolds

Abstract: A molecular rotor thioflavin T (ThT) is usually used as a fluorescent ligand specific for G-quadruplexes. Here, we demonstrate that ThT can tightly bind non-G-quadruplex DNAs with several GA motifs and dimerize them in a parallel double-stranded mode, accompanied by over 100-fold enhancement in the fluorescence emission of ThT. The introduction of reverse Watson–Crick T-A base pairs into these dimeric parallel-stranded DNA systems remarkably favors the binding of ThT into the pocket between G•G and A•A base pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 48 publications
5
39
0
Order By: Relevance
“…ThT was first reported in 2013 as a G4 ligand to study the human telomere G4 22AG [dAGGG(TTAGGG)3], and it was demonstrated to differentiate between G4, duplexes and single strands with high fluorescence intensity [87,95]. This fluorescence turn-on ligand has been widely applied as a sensor, for instance, for Ag + [96] and Hg + [97] detection, based on the interaction between the ligand and G4. ThT has also been applied as a label-free fluorescent turn-on ligand for sensing bio-thiols based on its ability to induce unique G4 structures [72], and it was demonstrated as a probing method for structural changes in i-motif (four stranded DNA secondary structures that consist of hemi-protonated and intercalated cytosine base pairs (C:C + )) [98].…”
Section: Fluorescent Turn-on G-quadruplex Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…ThT was first reported in 2013 as a G4 ligand to study the human telomere G4 22AG [dAGGG(TTAGGG)3], and it was demonstrated to differentiate between G4, duplexes and single strands with high fluorescence intensity [87,95]. This fluorescence turn-on ligand has been widely applied as a sensor, for instance, for Ag + [96] and Hg + [97] detection, based on the interaction between the ligand and G4. ThT has also been applied as a label-free fluorescent turn-on ligand for sensing bio-thiols based on its ability to induce unique G4 structures [72], and it was demonstrated as a probing method for structural changes in i-motif (four stranded DNA secondary structures that consist of hemi-protonated and intercalated cytosine base pairs (C:C + )) [98].…”
Section: Fluorescent Turn-on G-quadruplex Ligandmentioning
confidence: 99%
“…As shown in Table 1, unlike NMM, some G4 studies have indicated that ThT-induced G4s can potentially cause topological changes [101], producing false positive and false negative results [97]. It was also shown to bind tightly to non-G4 G–A-rich containing sequences and dimerise them into a parallel double-stranded modes [96]. Furthermore, ThT was found to be difficult to use for effective monitoring of G4s in the chromatin of live cells because of its inability to stain the nuclei [102].…”
Section: Fluorescent Turn-on G-quadruplex Ligandmentioning
confidence: 99%
“…Although G-runs are essential for G4 formation,37, 38, 39 other factors are critical, including G-poor loop sequences,40, 41, 42, 43 which may contain accessible antisense targets. The ability of ThT to bind to pockets between adenine pairs 26 would explain the observed high ThT signal for adenine-rich controls, particularly for GA8 and GA12 (Figure 1B). The correlation with predicted G scores can be further reduced by non-homogeneous structures in solution, including hairpins in equilibrium with G4s (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 97%
“…A selectivity of ThT for G4 structures has been demonstrated by large increments in the fluorescence emission at around 490 nm, which contrast to a low signal in the presence of double- or single-stranded DNA sequences or water controls 22 . Guanine is the most favorable nucleobase for ThT binding, although ThT bound to a non-G-quadruplex structure may also yield an elevated fluorescence signal 25, 26. Nevertheless, the ThT probe can specifically recognize RNA G4s that adopt, in an exclusive manner, all-parallel conformations independent of their sequences and experimental conditions 6, 27.…”
Section: Introductionmentioning
confidence: 99%
“…Some fluorescence probes that specifically recognize DNA sequences have been developed 2022. Fluorescence nanoparticles such as DNA-silver nanoclusters2326 and small organic dyes such as thioflavin T,2729 ethidium bromide (EtBr),30 thiazole orange (TO),31 TOTO,32 and iridium complex33 can bind to DNA chains and show various fluorescence properties depending on their manner of binding and binding ability. Some of them can distinguish ss-DNA from ds-DNA or G-quadruplex DNA.…”
Section: Introductionmentioning
confidence: 99%